A review on medicinal benefits of Persicaria minor/ Muhammad Firdaus Asanai ... [et al.] - Asanai, Muhammad Firdaus; Haron, Norhisham; Camalxaman, Siti Nazrina; Mohamed, Emida; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
Herbal plants have been documented to treat various types of disorder such as cold, fever and sore throat. Due to the revolution of treatment, chemical drugs have been developed to treat patients. However, prolong administration of chemical drugs has been claimed to contribute various side effects among chronic patients. Persicaria minor, locally known as kesum, is currently being used as a traditional remedy instead of using it as an additional aromatic flavor in food. The main focus of this study is to summarize the recent findings on medicinal benefits of the leave extract of P. minor. Several studies have demonstrated the ability of this plant in inhibiting the growth of common infection organisms including S. aureus, reducing oxidative stress in the body as well as its anti-proliferative property for cancer and tumor development. The plant extract also helps to protect cell tissues from abnormal conditions including ulcer. Furthermore, other studies also stated that the plant can reduce high blood pressure by inhibiting the activity of angiotensin-converting enzyme (ACE), enhance wound healing process and increase vitamin A in blood. Therefore, it can be stated that P. minor has many medicinal values, making it a strong potential therapeutic agent that can be used as an alternative for the current chemical drugs.